Environmental toxicology : selected entries from the Encyclopedia of sustainability science and technology - Laws, Edward A. , 1945- (Springer, 2013)
"Environmental Toxicology provides a detailed, comprehensive introduction to this key area of sustainability and public health research. The broad coverage includes sections on ecological risk assessment, monitoring, mechanisms, fate and transport, prevention, and correctives, as well as treatment of the health effects of solar radiation and toxicology in the ocean. The 23 state-of-the-art chapters provide a multi-disciplinary perspective on this vital area, which encompasses environmental science, biology, chemistry, and public health"